THE ROLE OF CHARACTER EDUCATION TO IMPROVE THE MORAL OF THE NATION - Astriani Lestari; Agus Miftakus Surur (Journal of Contemporary Islamic Education, 2021)
It has become a shared awareness that the world of education is a way that has been done by human beings throughout their lives to become a means of transmitting and transformation of both values ​​and science. Thus the strategic world of education as a means of transmission and transformation of values ​​and knowledge, so in order to instill and develop the character of this nation, it cannot be separated from the role played by the world of education. Character education is important for human life, so the role played by the education world must not only show moral knowledge, but also love and be willing to act morally. In addition to education in schools, of course education in the family becomes the most important thing in instilling character education in children. The environment is also very supportive of that, so in addition to the family, school and also a good environment will also be embedded in good character for children.With so life becomes a child who has good character who will be the successor to a nation that has high character.